2008
DOI: 10.1007/s12291-008-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lipid peroxidation and non-enzymatic antioxidants in pregnancy induced hypertension

Abstract: The present study was designed to evaluate the lipid peroxidation and non-enzymatic antioxidants in pregnancyinduced hypertension (PIH) compared with healthy normal pregnant and non-pregnant as controls. 75 cases were studied of which 25 were normal healthy controls (Group A), 25 healthy pregnant women (Group B) of third trimester and 25 were PIH (Group C) of the same trimester. In PIH, malondialdehyde a lipid peroxidation product was significantly increased as compared to normal pregnant and non-pregnant cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 13 publications
2
21
0
2
Order By: Relevance
“…This result correlates well with numerous studies undertaken at many institutes. In India, studies conducted by Adiga, Patil et al [5] and Krishna Menon S [6] at different institutes showed significant elevations in the levels of malondialdehyde in preeclampsia compared to normal pregnancy and nonpregnant females. Outside India also, various studies like those by Elesa Llusla [7], Madazli R et al, and Chamy et al [8] have all found significantly increased MDA levels in preeclampsia as compared to normal pregnancy and also in pregnancy as such compared to non-pregnant females.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…This result correlates well with numerous studies undertaken at many institutes. In India, studies conducted by Adiga, Patil et al [5] and Krishna Menon S [6] at different institutes showed significant elevations in the levels of malondialdehyde in preeclampsia compared to normal pregnancy and nonpregnant females. Outside India also, various studies like those by Elesa Llusla [7], Madazli R et al, and Chamy et al [8] have all found significantly increased MDA levels in preeclampsia as compared to normal pregnancy and also in pregnancy as such compared to non-pregnant females.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Results of the present study confirm increased oxidative stress during normal pregnancy and pregnancy-induced hypertension. Lipid peroxidetion may be an important factor in the pathogenesis of pregnancy-induced hypertension 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that polyunsaturated fatty acids are attacked by ROS and converted into lipid hydroperoxides as the initial factor leading to vascular endothelial dysfunction in PE (Howlander et al 2007; Kaur et al 2008; Hubel et al 1989; Davidge et al 1992; Mehendale et al 2008; Patil et al 2007). …”
Section: Introductionmentioning
confidence: 99%